Retinitis pigmentosa and sensorineural deafness associated with a de novo DHX16 mutation: case report - Wang, Lei; Gao, Jiyong; Sun, Meng; Fan, Li; Wang, Shuhua; Li, Xue; Gu, Shuangyu; Han, Bingjuan (Frontiers in Genetics, 2026)
BackgroundRetinitis pigmentosa and sensorineural deafness are two distinct clinical entities that can be caused by a variety of genetic mutations. The DHX16 gene, which encodes a protein involved in RNA processing, has been implicated in several genetic disorders. Here, we report a unique case of de novo DHX16 gene mutation presenting with both retinitis pigmentosa and sensorineural deafness.Case PresentationWe describe the story of two 2-year-old girls who presented with progressive vision loss and hearing impairment. Both of these cases presented with de novo heterozygous mutations in the DHX16 gene. The mutation sites were NM_003587 c.2474C>T and NM_003587.5 c.1360C>T. Ophthalmological examination disclosed the classic stigmata of retinitis pigmentosa, while audiologic assessment revealed bilateral sensorineural hearing loss. Genetic testing identified a de novo mutation in the DHX16 gene, which was not present in the patients’ family histories. The patients were managed with supportive care, including hearing aids to improve their quality of life.ConclusionThese cases highlight the importance of genetic testing in patients with combined retinitis pigmentosa and sensorineural deafness. Early identification of the underlying genetic mutation can facilitate appropriate management and genetic counseling for affected individuals and their families. Further research is needed to explore the pathophysiological mechanisms and potential therapeutic targets for DHX16-related disorders.